Management of early pregnancy loss by reproductive endocrinologists: does access to mifepristone matter? - Zachary S. Anderson, M.D.; Richard J. Paulson, M.D.; Brian T. Nguyen, M.Sc., M.D. (F&S Reports, 2024)
Objective: To describe patterns and variations in the medical and procedural management of early pregnancy loss (EPL) among reproductive endocrinology and infertility specialists, with attention to mifepristone use. Design: Cross-sectional. Setting: Online survey. Patients: Society for Reproductive Endocrinology and Infertility members. Intervention: Not applicable. Main Outcome Measure: Preferred management for EPL. Results: Of 101 completed surveys (response rate: 12.2%), 70.3% of respondents reported diagnosing EPL at least once per week. Half (50.5%) of respondents preferred medical management compared with 27.7% who preferred procedural management and 21.8% who preferred expectant management. Approximately one-quarter (26.7%) of respondents offer mifepristone for medical management of EPL. The most common reason cited for not prescribing mifepristone was a lack of access to the medication. Mifepristone prescribers were more likely to work in a hospital or university setting than private practice. Increasing years in practice was also associated with mifepristone use. The use of mifepristone for EPL did not vary by the respondent’s age, gender, prior abortion training, or practice region. Conclusion: The most effective method of medical management uses both mifepristone and misoprostol. However, nearly three-quarters of reproductive endocrinology and infertility physicians do not offer mifepristone, which may be linked to access issues.